Diaspora Players: Legal Issues, Nationalism, and National Identity in the Indonesian Elite Football System - Abrar, Abrar; Fitriani, Fitriani; Suryani, Suryani (Universitas Majalengka, 2025)
Citizenship conversion is no longer a new thing in the international world. However, in the field of sports, the case of the naturalized Indonesian national football team diaspora is still often debated. The introduction of foreign talents is supported by national policies to strengthen the Indonesian national team towards the World Cup. This paper examines several legal concepts and various phenomena from a sociological perspective, such as nationalism and national identity in the lives of diaspora football players. The aim is to make the exchange of football players’ citizenship a case that needs to be discussed in the current status quo of sports in Indonesia. This research is methodologically based on the analysis of the mainstream press of naturalized Indonesian diaspora football players between 2020 - 2025, official documents of the Indonesian Football Association (PSSI) and the Fédération Internationale de Football Association (FIFA), as well as a review of various literature in the form of books and journals to examine the case of naturalized football players in Indonesia in the context of globalization, migration, citizenship, nationalism and national identity. As an implication, the Indonesian national team is one step closer to the 2026 FIFA World Cup, which has never been achieved before; the enthusiasm of the Indonesian people to watch the match, both directly and indirectly, is very high, as well as many children who are interested in joining SSB because they see the progress of the Indonesian national team diaspora players. Recommendations from the research results are that naturalized diaspora players should be level A, still young, and play in the major league clubs of each country.